2015
DOI: 10.1371/journal.pgen.1005221
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Bone Morphogenetic Protein Signaling by Tetraspanins and Glycosphingolipids

Abstract: Bone morphogenetic proteins (BMPs) belong to the transforming growth factor β (TGFβ) superfamily of secreted molecules. BMPs play essential roles in multiple developmental and homeostatic processes in metazoans. Malfunction of the BMP pathway can cause a variety of diseases in humans, including cancer, skeletal disorders and cardiovascular diseases. Identification of factors that ensure proper spatiotemporal control of BMP signaling is critical for understanding how this pathway is regulated. We have used a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 105 publications
(162 reference statements)
3
55
0
Order By: Relevance
“…We have previously reported a weak Susm ( su ppression of the sm a-9 M lineage) phenotype in the tsp-12(ok239) null mutants, which is enhanced by tsp-14(RNAi) , but not by RNAi of any of the remaining 19 tsp genes in C . elegans [7]. To further determine mechanistically how TSP-12 and TSP-14 function in Sma/Mab signaling, we generated three deletion alleles of tsp-14 ( jj95 , jj96 and jj97 ) using the CRISPR/Cas9 system (Fig 1C; see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported a weak Susm ( su ppression of the sm a-9 M lineage) phenotype in the tsp-12(ok239) null mutants, which is enhanced by tsp-14(RNAi) , but not by RNAi of any of the remaining 19 tsp genes in C . elegans [7]. To further determine mechanistically how TSP-12 and TSP-14 function in Sma/Mab signaling, we generated three deletion alleles of tsp-14 ( jj95 , jj96 and jj97 ) using the CRISPR/Cas9 system (Fig 1C; see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we have previously shown that the small transmembrane tetraspanin proteins are important in promoting BMP signaling in C . elegans [7]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations